Partial structural characterization of the cytoplasmic hemoglobin of Nostoc commune UTEX 584 expressed in Escherichia coli - Thorsteinsson, Marc Victor (Virginia Tech, 1994)
Investigations into the nitrogen fixing apparatus in cyanobacterium Nostoc commune revealed a gene encoding for a hemoprotein, known as cyanoglobin. The cyanoglobin gene was isolated and subcloned into Escherichia coli previously. The study presented here encompasses the optimization of growth conditions for the transformed F. coli, with subsequent induction of cyanoglobin synthesis. These conditions were applied to large-scale (24-1) fermentor culture, permitting purification of approximately 200 mg cyanoglobin. Structural analyses, including absorption spectroscopy and circular dichroism, are presented. These studies indicate that cyanoglobin is a cytoplasmic hemoglobin with properties quite unlike those of leghemoglobin a and sperm whale myoglobin, which are used as references of comparison. For example, the optical spectral properties of oxycyanoglobin are different from those of leghemoglobin and sperm whale myoglobin. In addition, the met-form of cyanoglobin has characteristics of a low-spin hemoglobin, in contrast to the high-spin met-forms of sperm whale myoglobin and leghemoglobin . Unusually, the met- form of cyanoglobin fails to coordinate the strong-field ligands, cyanide and azide, at pH 7 and pH 9. The Soret region circular dichroism (CD) spectrum of cyanoglobin is unlike that of sperm whale myoglobin, yet is very similar to leghemoglobin , suggesting a similar heme environment in these two hemoproteins. Far-UV CD of cyanoglobin revealed alphahelical character comparable to that of sperm whale myoglobin and leghemoglobin . Cyanoglobin is the first monomeric hemoglobin detected in a prokaryote, raising questions concerning a possible role of cyanoglobin in early globin gene evolution. Master of Science